UPAYA MENINGKATKAN PEMAHAMAN KONSEPBAHASA INDONESIA DENGAN PENERAPAN PROGRAM REMEDIAL TUTOR SEBAYA PADA SISWA KELAS VI SDN 2 METRO BARAT TAHUN PELAJARAN 2009/2010 - maryam maryam (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
This research is used to determine the extent of the application of cooperative learning peer tutor in class VI Elementary School 2 Metro West, on the activities and student learning outcomes. Indicators used in the research activity determine the success of student learning is to look at the observation sheet of research about student learning activities undertaken in class. The success of the research activities of students in the use of cooperative methods of peer tutoring is if at least 80% of its students have acquired or have a high learning activities in accordance with the calculations on the observation sheet that has been created by researchers in this study. After the recapitulation sheet researcher and teacher observation of a partner or team teaching results obtained by 10 students or 27.78% of the students have a low learning activities, as many as seven students or 19.44% of its students have learning activities that are, 15 students or approximately 41.67% of its students have high learning activities and 7 students or 19.44% students have a very high learning activities, and 8 students or 22.22% of its students have learned a very low activity. So it can be concluded that the use of peer tutors learning model can improve learning activities optimally at six graders Negeri 2 Metro West Keywords: Understanding the concept of reading, learning model, Peer Tutor